Examining Climate Change, Tourism, and Sustainability in Small Islands, with Reference to the Balearic Islands, the Caribbean Islands, and the Pacific Islands - Briggita Faraneva Rujita (Gadjah Mada Journal of Tourism Studies, 2020)
Tourism has become an important part of the social and economic development of small islands. The distinct differences and peculiarities of small islands have significantly raised awareness of sustainable tourism practices in small islands. In this case, the study seeks to determine the extent to which tourism sustainability on small islands is threatened by climate change. Small islands, and thus tourism, are vulnerable to rising average annual temperatures, changes in precipitation, sea-level rise, and extreme events such as El Nino-Southern Oscillation, hurricanes, and flooding. The Cayman Islands, Mallorca, and the Galápagos Islands were chosen as representatives of the Caribbean Archipelago, Balearic Archipelago, and Pacific Archipelago, respectively, as references to this issue. This study is based on secondary data and employs a qualitative approach. Based on previous research, the findings show that climate change has primarily affected small islands in these three case studies in terms of environmental sustainability, which then creates challenges in terms of economic and social sustainability. Thus, climate change and sustainable tourism can be viewed as interconnected issues that must be addressed in small islands.